Recognizing Reality-Unification of Official and Parallel Market Exchange Rates - Gray, Simon (Washington, D.C. : International Monetary Fund, 2021)
Some central banks have maintained overvalued official exchange rates, while unable to ensure that supply of foreign exchange meets legitimate demand for current account transactions at that price. A parallel exchange rate market develops, in such circumstances; and when the spread between the official and parallel rates is both substantial and sustained, price levels in the economy typically reflect the parallel market exchange rate. 'Recognizing reality' by allowing economic agents to use a market clearing rate benefits economic activity without necessarily leading to more inflation. But a unified, market-clearing exchange rate will not stabilize without a supportive fiscal and monetary context. A number of country case studies are included; my thanks to Jie Ren for pulling together all the data for the country case studies, and the production of the charts.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet